Peter Landesmann, Anti-Judaism on the Way from Judaism to Christianity (Wiener Vorlesungen: Forschungen 5; Peter Lang: Frankfurt am Main et al., 2012) - Rosik, Mariusz (The Biblical Annals, 2015)
Book review: Peter Landesmann, Anti-Judaism on the Way from Judaism to Christianity (Wiener Vorlesungen: Forschungen 5; Peter Lang: Frankfurt am Main et al., 2012). Pp. 121 + VIII. $33.95. ISBN 978-3-631-62132-5 (Softcover).